(3HMhK GdJShjbs (3CSGdjH GdbjGS hGdJMdjd hGNJHGQ GdaQhVs - (3EOQjS(B, (3KGHJ YHOGdQMefs ((3eUQs (3GdOGQ GdLGeYjIs, 2005)
(3jJfGhd gPG GdcJGH GQHYI YTQ aUd Ydi GdJQJjH GdJGdj HMhK GdJShjb eaGgje CSGSjI ; GSGdjH GdbjGS h GdJMdjd h GNJjGQ GdaQhV ; YedjI GdHMK GdJShjbj ; JUeje GdHMK; eUGOQ GdHjGfGJ ; WQb LeY GdHjGfGJ GdGhdjI ; GdbjGS ; GLQGA GdYjfGJ, GdYjfGJ GdOGFeI JLgjR GdHjGfGJ dGZQGV GdJMdjd GdGMUGFj , CSGdjH JMdjd GdHjGfGJ UjGZI hENJHGQ GdaQhV , JbQjQ GdHMK GdJShjbj JWHjbGJ YeGjI dGSGdjH JMdjd GdfJZjQGJ GdeJYOOI hGNJHGQ GdaQhV aj HMhK GdJShjbs
Keywords: (3GdGbJUGOs; (3GdJShjbs